Tendencies in the Composition of Press Releases for the New Media - Karapenchev, Yordan (Media and Language, 2019)
The article offers analysis of 100 press releases, chosen according to the method of maximum variation (heterogeneous sampling), described by M. Patton. The research is referring to the work of J. Nilsen, who outlines three key characteristics of texts in the new media – compactness, segmentation and hypertextuality, and examines whether the same characteristics can be observed in the chosen type of copywriting texts, created for the needs of IMC – the press releases. The research shows that the three tendencies, described by J. Nilsen are all present in copywriting texts as well.